Dynamic Scoring: An Assessment of Fiscal Closing Assumptions. (May 2020) - Moore, Rachel; Pecoraro, Brandon
Analysis of fiscal policy changes using general equilibrium models with forward-looking agents typically requires a counterfactual adjustment to some fiscal instrument in order to achieve the debt sustainability implied by the government's intertemporal budget constraint. The choice of fiscal instrument can induce economic behavior unrelated to the policy change in models where Ricardian Equivalence does not hold. In this article, we use an overlapping generations framework to examine the effects of alternative fiscal closing assumptions on projected changes to economic aggregates following a change in tax policy, assessing the extent to which the bias associated with a particular fiscal instrument can be mitigated. While we find quantitative differences in projected macroeconomic activity across alternative fiscal instruments, these differences tend to shrink as the closing date is delayed. Ultimately, the choice of fiscal instrument becomes relatively unimportant if fiscal closing can be delayed sufficiently into the future.